KOMPARASI KARAKTERISTIK PENCAIRAN BATUBARA BANKO SELATAN DAN YALLOURN AKIBAT PERUBAHAN TEMPERATUR - Artanto, Yuli; Hartiniati, Hartiniati (Badan Pengkajian dan Penerapan Teknologi, 2007)
A coal liqueafaction test was carried out to investigate the reactivity of anIndonesian brown coal, called South Banko, and an Australian brown coal, calledYallourn. The liquefaction reaction was conducted to ascertain the effect ofreaction temperature on the reactivity of both brown coals and it represents onthe oil, CLB, CO+CO2 and C1 C4 yields. The result shows that South Banko coalis more reactive than Yallourn coal. South Banko coal gives a higher oil yieldthan that of Yallourn. Oil derived from South Banko coal increases as reactiontemperature rises. In contrast, oil derived from Yallourn decreased as reactiontemperature increased. This result indicated that South Banko has more labilestructure than that of Yallourn and it can easily break down the structure of SouthBanko coal. In term of hydrocarbon gas, Yallourn produces higher yield than thatof South Banko. This suggests that Yallourn coal has alkyl groups in its structure.It was also found that CO+CO2 yields are similar to both brown coals. SouthBanko has less CLB yield than that of Yallourn but the CLB yield of South Bankocoal is higher than that of Yallourn while temperature is increased to 470oC. Inshort, the study shows that South Banko coal is more reactive than that ofYallourn coal and it is very potential for the coal liquefaction feedstock.Kata kunci: batubara muda, Banko Selatan, Yallourn, distillate yield, CLB,CO+CO2,C1-C4, feedstock